Influence of Product Innovation And Business Management on the Welfare of the Fishing Community (Studi Kasus di Desa Bedono, Kecamatan Sayung, Demak) - Rinto Armoko; Septina Dwi Retnandari (Jurnal Maritim Polimarin, 2020)
This research, which is based on the findings of fishermen welfare problems in Bedono Village, Sayung District, Demak Regency, aims to determine the effect of product innovation and business management on the welfare of fishing communities. Determination of the sample using proportional random sampling method with a sample of 37 people. The hypothesis was tested using Multiple Linear Regression analysis, t test and mediation test with the help of the SPSS version 24.0 program. The data used in this study are primary data and the instrument is a questionnaire. The results showed that product innovation had no effect on the welfare of fishermen and business management had no effect on the welfare of fishermen either. Product innovation and business management have no effect on the welfare of fishermen. Suggestions in this study include increasing fishermen's knowledge and skills by providing coaching and courses. To improve physical health, there are needs to built more adequate health facilities and to make socialization program on adequate physical and environmental health from village officials.